Cyclic fatigue resistance of different continuous rotation and reciprocating endodontic systems - Fabio de Almeida-Gomes; Humberto Ramah Menezes de Matos; Rodrigo Ferreira Lopes Arrais Nunes; Ariel Moura Arrais; Claudio Ferreira-Maniglia; Marcelo de Morais Vitoriano; Eduardo Diogo Gurgel-Filho (Wolters Kluwer Medknow Publications, 2016)
Objective: The objective of this study is to compare the cyclic fatigue resistance of nine types of endodontic instruments of nickel-titanium. Materials and Methods: Five files of 25 mm of length of each group: Reciproc (RC) R25; WaveOne (WO) Primary; Unicone (UC) L25 25/0.06; K3XF 25/0.06; ProTaper Universal F2 (PTF2); ProTaper Next X2 (PTX2); Mtwo 25/0.06; BioRaCe 25/0.06; One Shape L25 25/0.06 were subjected to a cyclic fatigue resistance test on a mechanical apparatus. The mean fracture time was analyzed statistically by one-way analysis of variance and Tukey's honest significant difference post hoc test, with significance set at P< 0.05. Conclusion: It was observed that the groups PTX2, RC, R25, UC L25 25/0.06, and WO Primary presented greater cyclic fracture resistance than the other groups (P< 0.001).